Minister Hooper’s Melancholic Virtue - Hafezi, Najmeh; Amjad, Fazel Asadi; Ahmadian, Moussa (Mediterranean Journal of Social Sciences, 2012)
Hawthorne’s ‘The Minister’s Black Veil’ is one of his short stories whose protagonist has sunk in a gloomy depression.Since most of the male characters in such stories follow a procedure for a type of self awareness (this may happen out of theplot, as in Mr. Hooper whose insight has occurred before the story begins), the result of their journey within themselves isdarkness and depression. The present study sought the footprint of true virtue in drawing the character into such deep thoughtsthat resulted in his everlasting coverage of his face by a black veil. One of the best approaches which proved the truth of theminister’s virtue was the definition that Immanuel Kant presented through his Observations on the Feelings of the Beautiful andSublime. Kant made use of the theory of the four temperaments which influence human mental and behavioral traits. In hisattitude, a melancholy is, among the other personality, the most virtuous and capable for the feeling of the sublime. Inaccordance with the characteristics represented by Kant for each temperament, reverend Mr. Hooper is regarded as amelancholy. With his deep thoughts, most realistic insight, and black moods, the minister of the story exhibits a truly virtuouspersonality.